Ethics and science : an introduction - Briggle, Adam (Cambridge applied ethics)
"Who owns your genes? What does climate science imply for policy? Do corporations conduct honest research? Should we teach intelligent design? Humans are creating a new world through science. The kind of world we are creating will not simply be decided by expanding scientific knowledge, but will depend on views about good and bad, right and wrong. These visions, in turn, depend on critical thinking, cogent argument and informed judgement. In this book, Adam Briggle and Carl Mitcham help readers to cultivate these skills. They first introduce ethics and the normative structure of science and then consider the 'society of science' and its norms for the responsible conduct of research and the treatment of human and animal research subjects. Later chapters examine 'science in society' - exploring ethical issues at the interfaces of science, policy, religion, culture and technology. Each chapter features case studies and research questions to stimulate further reflection"--